1976
DOI: 10.1113/jphysiol.1976.sp011309
|View full text |Cite
|
Sign up to set email alerts
|

Temperature‐induced interconversion of alpha‐and beta‐adrenoceptors in the frog heart.

Abstract: SUMMARY1. The effect of ambient temperature on the properties of adrenoceptors mediating inotropic responses was assessed in isolated frog hearts on the basis of the effects and tissue uptake of ox-and fl-adrenoceptor antagonists.2. At temperatures of 230 C and above inotropic responses to adrenaline were antagonized by propranolol (0-4-4.0 uM), but were unaffected by phentolamine (26.5 AM) and were potentiated by phenoxybenzamine (POB) (0.7-29.5 AM). Below 170 C the activity of propranolol was reduced at leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1

Year Published

1977
1977
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(38 citation statements)
references
References 18 publications
2
35
1
Order By: Relevance
“…It has further been reported that at low temperature the fl-adrenoceptorblocking drug propranolol loses 90% of its potency as an antagonist of the inotropic effect of adrenaline on the frog heart (Kunos & Nickerson, 1976). The problem is that the time of treatment with propranolol was very short, which raises the question whether the receptor blockade was complete.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…It has further been reported that at low temperature the fl-adrenoceptorblocking drug propranolol loses 90% of its potency as an antagonist of the inotropic effect of adrenaline on the frog heart (Kunos & Nickerson, 1976). The problem is that the time of treatment with propranolol was very short, which raises the question whether the receptor blockade was complete.…”
Section: Introductionmentioning
confidence: 84%
“…For example, temperature reduction from 250C to 12°C caused a tenfold increase in the chronotropic potency of adrenaline in the perfused toad heart (Harri, 1973) but temperature reduction from 240C to 140C led to a tenfold crease in the inotropic potency of adrenaline in the frog isolated heart (Kunos & Nickerson, 1976). At 120C isoprenaline was more potent than phenylephrine in the perfused toad heart (Harri, 1973) and frog heart (Tirri, Harri & Laitinen, 1974); at 14°C isoprenaline was more potent than phenylephrine in the frog ventricle (Benfey, 1975).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…38 ' 42 The capacity to assess directly both species of receptors after interventions known to influence the relative magnitudes of the respective physiological responses to a-and ^-stimulation should be of use in resolving this provocative issue.…”
Section: Potential Future Usefulness Of Direct Radioligand Binding Tementioning
confidence: 99%